Towards Long-Term Population Decline: A Discussion of Relevant Issues (Vers un déclin à long terme de la population: discussion des questions pertinentes) - Reher, David S. (European journal of population, 2007)
This paper contains thoughts on the process of imminent population decline under way in much of the developed world and quite possibly in other world regions as well. We are witnessing the beginnings of a vast trend change which promises to bring to a close a period of population growth that has lasted for several centuries. It can be shown that this great change is a byproduct of the demographic transition that unleashed a number of the forces leading to where we are today. The extent to which much of the developing world will follow the reproductive trends of the developed world, with their social and economic implications, is discussed. The decades ahead for much of the world will lead us into mostly uncharted territory that bears few similarities with past periods of population decline. The purpose of this paper is to stimulate reflection and debate on a subject that looms as perhaps the key social issue of the twenty-first century. /// Cet article contient des réflexions sur le processus de déclin de la population, déjà en cours dans une grande partie du monde développé, et vraisemblablement dans le reste du monde. Nous assistons actuellement au début d'un retournement de tendance qui devrait mettre fin à une période d'accroissement de la population qui a duré plusieurs siècles. On peut montrer que ce grand changement est un produit de la transition démographique, qui a déclenché des phénomènes menant à la situation actuelle. La question de savoir dans quelle mesure les pays en développement s'aligneront progressivement sur les tendances en matière de reproduction du monde développé est discutée, avec toutes ses implications sociales et économiques. Les décennies à venir mèneront une grande partie du monde dans une ère encore inconnue, avec peu de points communs avec les périodes passées de déclin de la population. Le but de cet article est de stimuler la réflexion et le débat sur un sujet qui s'annonce comme le problème social clé du vingt-et-unième siècle.